Physiological and performance responses to the "FIFA 11+" (part 1): is it an appropriate warm-up? - Bizzini, M.; Impellizzeri, F. M.; Dvorak, J.; Bortolan, L.; Schena, F.; Modena, R.; Junge, A. (Journal of Sports Sciences, 2013)
The aim of the study was to examine the post-exercise effects of the "FIFA 11+" on various physical performance and physiological variables, to understand whether this programme is an appropriate warm-up for football players. Results were compared with the literature using a meta-analytical approach. Twenty amateur male football players [mean age 25.5 (s ± 5.1) years, body mass 75(8) kg, height 181(6) cm] participated in the study. They were tested twice before (control period) and once after the "FIFA 11+" for: 20-m sprints, agility, vertical jump, stiffness, isometric maximal voluntary contraction (MVC), rate of force development (RFD), and star excursion balance test. Oxygen uptake, lactate and core temperature were also measured.